Re-evaluation of the taxonomic confusion of the metallic-blue Pimpla Fabricius, 1804 (Hymenoptera: Ichneumonidae: Pimplinae) species in the Oriental region - Chen, Hsuan-Pu; Lin, Kai-Ti; Wu, Shipher (Zootaxa, 2023)
The metallic-blue body coloration is a distinct characteristic found in seven species of the cosmopolitan genus Pimpla Fabricius, 1804. In this study, we focus on two externally similar species, namely P. cyanator Morley, 1914 in India and P. alishanensis (Kusigemati, 1984) in Taiwan, along with the Indian P. indra Cameron, 1899, which are the only three species in the Oriental region exhibiting this trait. By examining the type series of these two taxa and acquiring additional materials from Taiwan, we discovered female morphological variations that resemble the form of the holotype of P. cyanator. Consequently, we propose that P. alishanensis should be synonymized with P. cyanator (syn. nov.). Furthermore, we provide a redescription of P. cyanator based on morphological characters and molecular COI sequences. We also discuss its revised distribution, the diagnostic features distinguishing P. cyanator from other metallic-blue Pimpla species worldwide, the factors influencing the color change in specimens, and some potential misidentifications that have occurred in the past.